Zinc‐oxide nanoparticles act catalytically and synergistically with nitric oxide donors to enhance antimicrobial efficacy. Issue 7 (5th March 2019) - Singha, Priyadarshini; Workman, Christina D.; Pant, Jitendra; Hopkins, Sean P.; Handa, Hitesh
Abstract: The development of infection‐resistant materials is of substantial importance as seen with an increase in antibiotic resistance. In this project, the nitric oxide (NO)‐releasing polymer has an added topcoat of zinc oxide nanoparticle (ZnO‐NP) to improve NO‐release and match the endogenous NO flux (0.5–4 × 10 −10 mol cm −2 min −1 ). The ZnO‐NP is incorporated to act as a catalyst and provide the additional benefit of acting synergistically with NO as an antimicrobial agent. The ZnO‐NP topcoat is applied on a polycarbonate‐based polyurethane (CarboSil) that contains blended NO donor, S ‐nitroso‐ N ‐acetylpenicillamine (SNAP). This sample, SNAP‐ZnO, continuously sustained NO release above 0.5 × 10 −10 mol cm −2 min −1 for 14 days while samples containing only SNAP dropped below physiological levels within 24 h. The ZnO‐NP topcoat improved NO release and reduced the amount of SNAP leached by 55% over a 7‐day period. ICP‐MS data observed negligible Zn ion release into the environment, suggesting longevity of the catalyst within the material. Compared to samples with no NO‐release, the SNAP‐ZnO films had a 99.03% killing efficacy against Staphylococcus aureus and 87.62% killing efficacy against Pseudomonas aeruginosa . A cell cytotoxicity study using mouse fibroblast 3T3 cells also noted no significant difference in viability between the controls and the SNAP‐ZnO material, indicating no toxicity toward mammalian cells. The studies indicate that the synergy of combining a metal ion catalyst with a NO‐releasing polymer significantly improved NO‐release kinetics and antimicrobial activity for device coating applications. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 00A: 000–000, 2019.